DATA TRANSPARENCY AND INFORMATION SHARING: CORONAVIRUS PREVENTION PROBLEMS IN INDONESIA - Sofia Al Farizi; Bagus Nuari Harmawan (Universitas Airlangga, 2020)
Background: Information and data of coronavirus outbreak from central government shared publicly was lacking. Such the lack of information and data has several negative impacts, such as confusion about the information experienced by local governments in accessing positive case data at the beginning of the pandemic and the red zone of the spread of the corona virus,